Dampak Perubahan Tata Guna Lahan dan Implikasinya terhadap Besaran Debit Banjir pada Kawasan Ekonomi Khusus (KEK) Mandalika: Impact of Land Use Change and its Implications for Flood Discharge in the Mandalika Special Economic Zone (SEZ) - Muh Bagus Budianto; Bambang Harianto; Salehudin Salehudin; Hartana Hartana; Syamsul Hidayat (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2022)
Land use change is one of the factors that affect changes in flood discharge in watersheds. Currently, the Mandalika Resort area has been designated as a Special Economic Zone (SEZ) so that large-scale development occurs in the Mandalika area with an area of 1,035.67 Ha. The purpose of this study was to determine the effect of changes in land use at the Mandalika resort on flood discharge in the watersheds in the Mandalika SEZ, namely the Balak, Ngolang and Tabelo watersheds. The data used are rainfall data, watershed maps and land use. Rainfall data is needed for analysis of hourly rainfall distribution, the method used is the Alternating Block Method (ABM). Land use maps and their changes are used to obtain Curve Number (CN) values. These parameters are used as input into the HEC-HMS software. The results of the analysis show that changes in land use have caused the CN value of the Balak watershed to increase by 1,33% in 2030 and increase by 3,72% in 2045, the CN value of the Ngolang watershed increase by 3,24% in 2030 and increase by 6,49% in 2045 and the value of the CN DAS Tableo will increase by 0,12% in 2030 and increase by 0,59% in 2045. Changes in land use have also resulted in an increase in flood discharge at various return periods. In the Balak watershed it will increase by an average of 1,76% in 2030 and 4,94% in 2045, the flood discharge in the Ngolang watershed will increase by an average of 4,00% in 2030 and 8,67% in 2045 and in the Tebelo watershed it will increase by an average 0,17% in 2030 and 0,79% in 2045.